Alexander - Stone, Oliver
Conquering 90% of the known world by the age of 25, Alexander the Great (Farrell) led his armies through 22, 000 miles of sieges and conquests in just eight years. Coming out of tiny Macedonia, Alexander led his armies against the mighty Persian Empire, drove west to Egypt, and finally made his way east to India. This film will concentrate on those eight years of battles, as well as his relationship with his boyhood friend and battle mate, Hephaestion. Alexander died young, of illness, at 33. Alexander's conquests paved the way for the spread of Greek culture (facilitating the spread of Christianity centuries later), and removed many of the obstacles that might have prevented the expansion of the Roman Empire. In other words, the world we know today might never have been if not for Alexander's bloody, yet unifying, conquest.